In situ microbial remediation of crude oil-soaked marine sediments using zeolite carrier with a polymer coating. Issue 1 (April 2018) - Zhao, Guoqiang; Sheng, Yanqing; Wang, Chuanyuan; Yang, Jian; Wang, Qiaoning; Chen, Lingxin
Abstract: Marine oil spill pollution is an important environmental problem in the world, especially crude oil-soaked marine sediments, because they are difficult to be remediated. In this study, in situ bioremediation of oil-soaked sediment was performed in the middle of the Bohai Sea. Oil-degrading bacteria were adsorbed on powdery zeolite (PZ)/granular zeolites (GZ) surfaces and then wrapped with poly-γ glutamic acid (γ-PGA). Settling column and wave flume experiments were conducted to model marine conditions and to select appropriate biological reagents. The optimal conditions were as follows: the average diameter of GZ 3 mm, mass ratio of GZ/PZ 2:1, and concentration of γ-PGA 7%. After bioremediation, over 50% of most oil-spilled pollutants n -alkanes (C12 to C27 ) and polycyclic aromatic hydrocarbons were degraded in 70 days. This work resulted in a successful trial of in situ bioremediation of oil-soaked marine sediments. Graphical abstract: Highlights: Bacterial agents, zeolite and poly glutamic acid were applied in marine sediment remediation. Coated zeolite decreased the loss of effective bacteria during the delivery process. Over 50% of crude oil-spilled pollutants were degraded in 70 days.